Sex differences in acute translational repressor 4E-BP1 activity and sprint performance in response to repeated-sprint exercise in team sport athletes - Dent, J. R.; Edge, J. A.; Hawke, E.; McMahon, C.; Mündel, T. (Journal of Science and Medicine in Sport, 2015)
Objectives: The physiological requirements underlying soccer-specific exercise are incomplete and sex-based comparisons are sparse. The aim of this study was to determine the effects of a repeated-sprint protocol on the translational repressor 4E-BP1 and sprint performance in male and female soccer players. Design: Cross-over design involving eight female and seven male university soccer players. Methods: Participants performed four bouts of 6× 30-m maximal sprints spread equally over 40 min. Heart rate, sprint time and sprint decrement were measured for each sprint and during the course of each bout. Venous blood samples and muscle biopsies from the vastus lateralis were taken at rest, at 15 min and 2 h post-exercise. Results: While males maintained a faster mean sprint time for each bout (P < 0.05) females exhibited a greater decrement in sprint performance for each bout (P < 0.05), indicating a superior maintenance of sprint performance in males, with no sex differences for heart rate or lactate. Muscle analyses revealed sex differences in resting total (P < 0.05) and phosphorylated (P < 0.05) 4E-BP1 Thr37/46, and 15 min post-exercise the 4E-BP1 Thr37/46 ratio decreased below resting levels in males only (P < 0.05), indicative of a decreased translation initiation following repeated sprints. Conclusions: We show that females have a larger sprint decrement indicating that males have a superior ability to recover sprint performance. Sex differences in resting 4E-BP1 Thr37/46 suggest diversity in the training-induced phenotype of the muscle of males and females competing in equivalent levels of team-sport competition.